The Oncomodulatory Role of Human Cytomegalovirus in Colorectal Cancer: Implications for Clinical Trials - Chen, Hsin-Pai; Chan, Yu-Jiun (Frontiers in Oncology, 2014)
Increasing evidence suggests that human cytomegalovirus (HCMV), a beta-herpes virus that chronically infects human, is associated with colorectal cancer (CRC). The viral nucleic acids specifically localized to the neoplastic mucosal epithelium of CRC, while tumoral presence of HCMV independently predicted a poor outcome in elderly patients. In the past decade, the concept of “oncomodulation” of HCMV in human cancers has been formulated. In CRC, changes in the tumor microenvironment are closely related to cancer behavior and prognosis, while the underlying mechanism driving these changes remains unclear. Since HCMV affects multiple cellular functions, including signal pathways that regulate angiogenesis, apoptosis, cell invasiveness and anti-cancer immunity, the virus potentially exerts oncomodulatory effects in the tumor microenvironment of CRC. Here, we summarize the current knowledge about the association between HCMV and CRC and suggest future perspectives on both research and anti-cancer therapy of CRC.